University of Florida Potato Variety Trials Spotlight: ‘Harley Blackwell’ - Rodrick Z. Mwatuwa; Christian T. Christensen; Pam Solano; Kathleen G. Haynes; Lincoln Zotarelli (EDIS, 2017)
by Rodrick Z. Mwatuwa, Christian T. Christensen, Pam Solano, Kathleen G. Haynes, and Lincoln Zotarelli http://edis.ifas.ufl/edu/hs1298